Opportunities for cancer prevention at syringe services programs: acceptability of HPV self-sampling and vaccination among people who inject drugs - Samuel Hinkes; Katrina Ciraldo; Erin Kobetz; Tyler S. Bartholomew; Sarah Rinehart; Nicolette Siringo; Rebecca Barnett; Neha Godbole; Frantzia Jeanty; Morgan Frederick; Hansel E. Tookes (BMC, 2024)
Abstract Introduction Despite having a high risk of acquiring sexually transmitted infections, people who inject drugs (PWID) often do not receive recommended HPV screenings due to barriers to healthcare. Guideline-based cervical HPV screening and vaccination can prevent cervical cancer. Low-cost, low-barrier methods for cancer screening and prevention are important for vulnerable communities such as PWID. Methods We examined acceptability of HPV self-sampling at a syringe services program (SSP). Participants with a cervix (n = 49) participated in patient education followed by a survey to assess willingness to perform HPV self-sampling versus standard of care. Results 59% found self-sampling to be acceptable, citing privacy, ease, and quickness. Among those opting for HPV screening delivered by a provider (n = 16), participants cited concerns about adequate sampling (81%) and test accuracy (75%). Notably, only 18% of participants reported complete HPV vaccination. Conclusion Cervical HPV self-sampling was acceptable to PWID. SSP-based efforts to provide preventative health services could place tools for cancer screening into the hands of PWID, a need-to-reach community.